Tracking Aquatic Invaders: Autonomous Robots for Monitoring Invasive Fish - Tokekar, P.; Branson, E.; Vander Hook, Joshua; Isler, V. (IEEE robotics & automation magazine, 2013)
Carp is a highly invasive bottom-feeding fish that pollutes and dominates lakes by releasing harmful nutrients. Recently, biologists started studying the behavior of carp by tagging the fish with radio emitters. The biologists search for and localize the radio-tagged fish manually using a global positioning system (GPS) and a directional antenna. We are developing a novel robotic sensor system in which human effort is replaced by autonomous robots capable of finding and tracking tagged carp. In this article, we report the current state of our system. We present a new coverage algorithm for finding tagged fish and active localization algorithms for precisely localizing them. In addition to theoretical analysis and simulation results, we report results from field experiments.